Development of a New Silica Aerogel-Polypropylene Foam Composite as a Highly Flexible Thermal Insulation Material - Yoda, Satoshi; Takeshita, Satoru; Ono, Takumi; Tada, Ryosuke; Ota, Hideo (Frontiers in Materials, 2021)
A new flexible thermal insulation sheet, a composite of silica aerogel with polypropylene (PP) foam, has been developed. Even though a large volume ratio of silica aerogel (97%) was included, the composite showed high flexibility. Thermal conductivity of the composite was 0.016 W/(m⋅K) at 298 K, which is as low as silica aerogel monolith. Silica aerogel flaking, which has been a problem in practical applications, is very low in this composite due to skin layers of the polymer-foam composite. A supercritical drying process for rolled sheets of the material for large-scale production is also described. Simulations of extraction of 2-propanol from a silica alcogel revealed that rolled composite sheets with small spaces between the sheet composite are able to dry in a reasonable extraction time. These findings led to effective on production of this material on a pilot industrial scale.